2008
DOI: 10.1111/j.1572-0241.2008.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Colonic Manometry in Pediatric Slow Transit Constipation shows Significant Reductions in Antegrade Propagation

Abstract: Prolonged pancolonic manometry in children with STC showed significant impairment in antegrade propagating motor activity and failure to respond to normal physiological stimuli. Despite this, HAPS occurred with normal frequency. These findings suggest significant clinical differences between STC in children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 34 publications
3
53
1
Order By: Relevance
“…When the trial was designed, the optimal parameters (if any) were unknown, and hence were selected on arbitrary criteria. Having demonstrated a statistical improvement in transit times [7], 24-hour colonic manometry [11], and quality of life [6,10] in the trial, the current study aimed to find out whether more frequent TES treatment might further improve function.…”
Section: Discussionmentioning
confidence: 98%
“…When the trial was designed, the optimal parameters (if any) were unknown, and hence were selected on arbitrary criteria. Having demonstrated a statistical improvement in transit times [7], 24-hour colonic manometry [11], and quality of life [6,10] in the trial, the current study aimed to find out whether more frequent TES treatment might further improve function.…”
Section: Discussionmentioning
confidence: 98%
“…Colonic manometry is used by many practitioners to evaluate idiopathic constipation [19,20]. Our experience with this modality demonstrated inconsistent results [4].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the study of King and colleagues (11), it was identified that in children with STC there was a significant impairment in antegrade propagating activity, with no change in the frequency of high-amplitude propagating sequences. Also, King et al reported deficient or absent responses to physiological stimuli.…”
Section: Comparison Of the Characteristics Of Cmcs Recorded In Human mentioning
confidence: 97%
“…A number of studies have made attempts to identify mechanisms underlying the onset of STC, but no clear underlying mechanism has yet been determined. There is evidence that a population of patients with STC have reduced numbers of high-amplitude propagating contractions (2,11). There is also evidence that the interval between CMCs is reduced in the transverse colon and splenic flexure (9).…”
mentioning
confidence: 99%